The Impact Of Diorama’s Use Of Media On Learning Results Cognitive Science Matter In Ecoseries Class V Sdn Singapadu To Curug City Attack Banten In 2020/2021 Killing Buffen - Umi Hanifah (Desanta Publisher, 2020)
This study aims to determine whether there is an influence from the use of DIORAMA media on the cognitive learning outcomes of ecosystem material in class V SDN Singapadu Curug Serang City Banten in 2020-2021. The type of research used by the researcher is quantitative research, experimental method with the type of pre-experimental design (non-design). The form taken is a one-goup pretest-posttest design. The instrument used in this study is a test with 20 multiple choice questions. questions and observations of students and teachers. The population of students studied in this study were 20 students with 8 male students and 12 female students. Based on the results of the study, it can be seen that the results of cognitive science learning before being treated using the DIORAMA media and tested using the pre-test the average value was 38.30. This value is included in the low category and the majority of students' pre-test learning outcomes are in the low category, namely 65% ​​or as many as 13 students. This is possible because children are less interested in the simple picture media used by the teacher. Meanwhile, after being treated using DIORAMA media and doing a post-test, it can be seen that the average score of students changed to 65.95, and this is included in the medium category. The highest score is 87.00 (very high category). And the lowest value is 47.00 (low category). The majority of students' post-test learning outcomes are in the moderate category, which is 55% or as many as 11 students. So it can be concluded that this study has the effect of using the DIORAMA media on the cognitive learning outcomes of ecosystem material for the fifth grade students of SDN Singapadu Curug Serang Banten City in 2020-2021 because it has an increase in the value of learning outcomes as much as 40%.